P PERAN PERPUSTAKAAN GRAHA WIDYA MANDALA DALAM MENINGKATKAN PRESTASI SISWA SMA NEGERI 1 SNGARAJA: MENINGKATKAN PRESTASI SISWA SMA NEGERI 1 SINGARAJA - Purnami, Kadek Wulan (ACARYA PUSTAKA, 2024)
Abstract The purpose of this study is; (1) To find out more deeply and to be able to obtain data on the role of libraries in improving student achievement at SMA Negeri 1 Singaraja, (2) To find information on the obstacles and challenges of libraries in improving student achievement at SMA Negeri 1 Singaraja. This study uses a qualitative descriptive research method and the informant determination technique uses purposive sampling. The author chose the research location, namely SMA Negeri 1 Singaraja. In this study, the researcher used observation, interview, and document study techniques to collect data in obtaining concrete data. From the research results obtained, the researcher found that in improving student achievement, the Graha Widya Mandala library provides a library collection as a support for competition activities followed by students. In addition, discussion room facilities are also provided for students and teachers as a supporting facility for competition activities followed by students. However, there are still challenges in improving student achievement, namely due to limited library space and inconsistent weeding activities. Keywords : Library, Achievement, Collection, Student